TRANSLANGUAGING THROUGH THE LENS OF SOCIOCULTURAL APPROACH : STUDENTS’ ATTITUDES AND PRACTICES - Wulandari Santoso (Jurnal Pendidikan Bahasa, 2020)
Recent research developments have an increased focus on the complexity and the dynamic nature of language practices. Translanguaging views multilingual speakers as having one integrated language repertoire which they can use strategically to communicate and involve in the process of meaning-making activities. This research aims to investigate attitudes and practices of translanguaging among English department students in the Language Assessment course at Universitas Bunda Mulia, Jakarta. A series of observations and semi-structured interviews were used to collect data to five students. The data were interpreted using a thematic analysis and critically evaluated using the sociocultural theory of mind. This research revealed that the students translanguaged not only for cognitive functions, but also for creative and critical linguistic practices. Positive attitudes were also demonstrated through the students’ active participation in using their full repertoires. Further pedagogical implications in this particular context are also discussed.